Indian Capital Market - Great Investment Story, A Fundamental Approach - Jain, Garima (2006)
The dissertation aims to evaluate the growth prospects in the Indian stock market. The study is conducted by analyzing the three growth sectors of the Indian economy namely Information Technology, Textile industry and Capital Goods and Equipment industry. The backbone of the research is four companies in each sector whose financial statements of last three years have been closely studied and with a fundamental approach the coming years profits have been forecast. Further, P/E multiple has also been forecast adjusted for any re-rating wherever found necessary. The study clearly establishes a good growth in the share prices of these companies if invested now.